Pedagogy of Peace and Philosophy of War: the Search for Truth - Serhiy Klepko (International Society of Philosophy and Cosmology, 2017)
Peace pedagogy (German: Friedenspedagogik) and the Peace education are identified as relevant educational paradigm and set of educational projects aimed at solving problems of teaching non-violence and the capacity for peace in the context of the democratic movement for peace. There is a set of reasons to state that the education system of the world depends not only on technological trends and mastering the sum of strategies of war and peace but, first of all, on what extends the whole education is true for its subjects and able to provide research on the ultimate question of social and personal life, including eternal mankind's dream for peace. This paper describes methodological role for pedagogy of peace of geophilosophy as a concept to solve socio-economic conflicts in the dimensions of truth and earthly life in which modern geophilosophical research carried out to find a man's place in the world and territory for him